Change Agents or Cogs in the Machine? Female Managers and Unofficial Gender Equality in Federal Agencies. Issue 2 (3rd April 2018) - Marvel, John D.
ABSTRACT: This article combines administrative personnel data with survey data to examine whether increases in female representation among the managerial ranks of federal agencies are associated with increases in unofficial gender equality in those agencies. Specifically, female representation at multiple levels of agencies' personnel hierarchies are measured so as to examine whether these measures are associated with increases in lower-level female and male employees' subjective experiences of power, status, and opportunity. The results indicate that female representation among the SES has salutary effects on General Schedule (GS) level 7–12 and General Schedule level 13–15 females. Additionally, the results suggest that female representation among GS 13–15 supervisors has salutary effects on GS 7–12 females. Finally, the results suggest that top-level female representation has negative effects on GS 7–12 males. These findings speak to the ongoing theoretical debate concerning female managers' ability and willingness to bring about equality-inducing change in their organizations. They also speak to the question of whether a representative bureaucracy has unfavorable distributional consequences for members of nonminority groups.